2020
DOI: 10.3389/fpsyg.2020.590559
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Measurement in a Post Covid-19 World: Psychometric Properties and Invariance of the DASS-21 in Athletes and Non-athletes

Abstract: Psychological science faces a call to action researching the implications of the corona virus disease 2019 pandemic. Rapid reviews have reported that maintaining rigorous research standards is a priority for the field, such as ensuring reliable and valid measurement, when investigating people's experience of Covid-19 (O'Connor et al., 2020). However, no research to date has validated a measure mental health symptomology for an athlete population. The current research addresses this gap by examining the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 59 publications
4
72
0
4
Order By: Relevance
“…The results of many studies have demonstrated that limited physical activity due to the lockdown can be related to a number of negative metabolic effects that rapidly increase the risk of the occurrence of many serious diseases i.e., diabetes, osteoporosis, cardiovascular diseases, or cancer [ 46 , 47 , 48 , 49 , 50 , 51 ]. Additionally, limited activity and related decreases in athletes’ fitness can have a negative impact on the psychological domain of both athletes and non-athletes, eventually leading to depression or PTSD symptoms [ 52 , 53 ]. Accumulation of all these factors can result in serious psychological and somatic consequences that could even exclude the participants from future competitions and, according to the HRF concept, can have a negative effect on their health.…”
Section: Discussionmentioning
confidence: 99%
“…The results of many studies have demonstrated that limited physical activity due to the lockdown can be related to a number of negative metabolic effects that rapidly increase the risk of the occurrence of many serious diseases i.e., diabetes, osteoporosis, cardiovascular diseases, or cancer [ 46 , 47 , 48 , 49 , 50 , 51 ]. Additionally, limited activity and related decreases in athletes’ fitness can have a negative impact on the psychological domain of both athletes and non-athletes, eventually leading to depression or PTSD symptoms [ 52 , 53 ]. Accumulation of all these factors can result in serious psychological and somatic consequences that could even exclude the participants from future competitions and, according to the HRF concept, can have a negative effect on their health.…”
Section: Discussionmentioning
confidence: 99%
“…The DASS-21 is a popular measure of mental health ( 20 , 21 ), and with its 21 items (7 items for each subscale) and three dimensions with similar psychometric properties is based on the tripartite model of depression, anxiety, and stress. Each 7-item subscale is rated on a 4-point Likert scale ranging from 0 (Did not apply to me at all) to 3 (Applied to me very much).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, DASS-21 assessed three domains (i.e. anxiety, depression and stress) and its psychometric properties was validated across clinical and non-clinical samples in different cultures and languages during the COVID-19 pandemic [19]. In this study, the Cronbach's alpha (internal consistency) for different versions of DASS-21 is as follows: stress scale ranges from 0.839-0.934, anxiety scale ranges from 0.784-0.914, and depression scale ranges from 0.878-0.943.…”
Section: Measures and Instrumentsmentioning
confidence: 99%